Chemoselective probe for detailed analysis of ketones and aldehydes produced by gut microbiota in human samples. Issue 62 (9th July 2019) - Conway, Louis P.; Garg, Neeraj; Lin, Weifeng; Vujasinovic, Miroslav; Löhr, J.-Matthias; Globisch, Daniel
Abstract : New chemoselective method permits detection of 112 metabolic ketones and aldehydes in human samples due to significantly increased mass spectrometric sensitivity. Abstract : New strategies are required for the discovery of unknown bioactive molecules produced by gut microbiota in the human host. Herein, we utilize a chemoselective probe immobilized to magnetic beads for analysis of carbonyls in human fecal samples. We identified 112 metabolites due to femtomole analysis and an increased mass spectrometric sensitivity by up to six orders of magnitude.